Preliminary Evaluation of the Antibacterial Activity of an Ethanolic Extract from Commercial Chlorella vulgaris Powder Against Two Reference Bacterial Strains (Al-Farooq Journal of Sciences, 2026)
Antibiotic resistance is a growing clinical challenge, particularly among Klebsiella pneumoniae and Staphylococcus aureus, prompting interest in natural antimicrobial agents such as microalgae. To evaluate the in vitro antibacterial activity of an ethanolic extract prepared from commercial Chlorella vulgaris powder against reference strains of K. pneumoniae (ATCC 13883) and S. aureus (ATCC 25923). Three extract concentrations (100, 50, and 10 mg/mL) were tested using the disk diffusion method alongside standard antibiotics, in triplicate. Total inhibition diameters were recorded, and the 6 mm disk diameter was subtracted to obtain net inhibition zones. Data were analysed by two-way ANOVA with Tukey's HSD post-hoc test. Treatment significantly affected inhibition zone size (F(6,28) = 262.58, P < 0.001), while bacterial species alone had no significant effect (P = 0.456) and the treatment × species interaction was not significant (P = 0.114). A dose-dependent increase was observed; at 100 mg/mL, mean net inhibition zones reached 12.33 ± 2.52 mm for K. pneumoniae and 10.33 ± 1.53 mm for S. aureus. The ethanolic extract of commercial C. vulgaris powder exhibited detectable, dose-dependent antibacterial activity against both reference strains, warranting further MIC, MBC, and chemical characterisation studies.
Keywords: antibacterial activity, Chlorella vulgaris, disk diffusion, ethanolic extract, microalgae, preliminary screening